Lessons to be the King's Chronicler: a study of the Dialogos sobre quem deve ser o cronista do principe [Discussions about who should be the prince's chronlicer], by Pedro de Navarra - Granduque Jose, Maria Emilia [UNESP] (Programa Pos-graduacao Historia Univ Estado Do Rio De Janeiro, 2020)
In sixteenth-century Spain, scholars published a series of texts aimed at defining both the rules that should guide the writing of history and the desired qualities of a good chronicler. The authors of these works argued that the image of a kingdom, and, consequently, its ruler, was formed based on the writings of those scholars in charge of recording the past. This study analyses Pedro de Navarra's 1565 text Dialogos qual debe ser el chronista del principe in an effort to understand how scholars defined the positions of chronicler and historian in Spanish society during this period. In addition, this article presents an annotated translation of Dialogos in order to bolster analysis of the king's chronicler's assigned functions and requirements.
Keywords: Spain; 16th century; Pedro de Navarra; Dialogues; chronicler